Structural properties, electric response and magnetic behaviour of La2SrFe2CoO9 triple complex perovskite. (February 2016) - Casallas, F; Vera, E; Landínez, D; Parra, C; Roa, J
Abstract: The triple perovskite La2 SrFe2 CoO9 was prepared by the solid state reaction method from the high purity precursor powders La2 O3, SrCO3, Fe2 O3, Co2 O3 (99.9%). The crystalline structure was studied by X-ray diffraction experiments and Rietveld refinement analysis. Results reveal that this material crystallizes in an orthorhombic triple perovskite belonging to the space group Pnma (#62) with lattice constants a=5.491978(2)Ǻ, b=7.719842(2)Ǻ and c=5.436260(3)Ǻ. The granular surface morphology was studied from images of Scanning Electron Microscopy. The electric response was studied by the Impedance Spectroscopy technique from 10.0mHz up to 0.1MHz, at different temperatures (77-300K). Measurements of magnetization as a function of temperature permitted to determine the occurrence of a paramagnetic - ferromagnetic transition for a Curie temperature of 280K, which suggests it application in nanoelectronic devices. From the fit of the magnetic response with the Curie- Weiss equation it was concluded that the effective magnetic moment is particularly large due to the contribution of La, Fe and Co cations.